TINJAUAN YURIDIS METERAI DALAM KEABSAHAN SURAT PERJANJIAN TERHADAP PEMBUKTIAN HUKUM ACARA PERDATA - Prasetyanov, Yudha (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Binding is broader in scope than an engagement/agreement/contract, because binding is not only born from an engagement/agreement/contract, but binding is also born from the law. Binding contains 4 elements, which include: 1) A legal relationship, which attaches rights to one party and obligation to the other party; 2) Wealth, which means that the criteria of binding are measures that can have value in a legal relationship; 3) Parties, which means that in binding must consist of two or more people; 4) Prestasi or also known as kontraprestasi is part of the implementation of the binding, which according to Article 1234 of KUHPerdata is distinguished from giving something, doing something, and not doing something. This normative legal research is using a statute approach, conceptual approach, and comparative approach. Whether an agreement is valid or not can be traced to Article 1320 of the KUHPerdata , as well as the absence of a stamp duty in the agreement letter does not make an agreement that has been agreed invalid, or void by law. The agreement letter that fulfills the elements of the valid requirements of the agreement, will becomes law for the parties (pacta sunt servanda principle). Regarding to make an agreement letter that does not have a stamp duty to be used as evidence, then payment of stamp duty is made.Keywords: stamp duty, binding, agreement.